The Influence of the Reciprocal Teaching Learning Model Assisted by Student Worksheets (LKPD) on Students Mathematical Communication Ability - Sari, Ratih Puspita; Turmuzi, Muhammad; Kurniawan, Eka; Sarjana, Ketut (Balai Publikasi Indonesia, 2025)
This research aims to determine whether there is an influence of the reciprocal teaching learning model assisted by Student Worksheets (LKPD) on the mathematical communication skills of students at Senior High School 7 Mataram for the 2023/2024 academic year. This research is included in quantitative research with a quasi-experimental design research type with a posttest-only control design. The population in this study were all class X students at Senior High School 7 Mataram for the 2023/2024 academic year with samples from classes X.K and the instruments in this research are observation sheets and tests of mathematical communication skills as well as data analysis techniques using valid tests, namely the normality test, homogeneity test and hypothesis test. The results of this research show that there is a difference in the average value of the mathematical communication skills of students who use the reciprocal teaching learning model assisted by LKPD and students who use the conventional learning model. So this shows that there is an influence of the reciprocal teaching learning model assisted by Student Worksheets (LKPD) on the mathematical communication skills of students at Senior High School 7 Mataram in the 2023/2024 academic year